Directional Local Field Potentials in the Subthalamic Nucleus During Deep Brain Implantation of Parkinson’s Disease Patients - Nguyen, T. A. Khoa; Schüpbach, Michael; Mercanzini, André; Dransart, Alain; Pollo, Claudio (Frontiers in Human Neuroscience, 2020)
Segmented deep brain stimulation leads feature directional electrodes, that allow for a finer spatial control of electrical stimulation compared to traditional ring-shaped electrodes. These segmented leads have demonstrated enlarged therapeutic windows and have thus the potential to improve the treatment of Parkinson’s disease patients. Moreover, they provide a unique opportunity to record directional local field potentials. Here, we investigated whether directional local field potentials can help identify the best stimulation direction to assist device programming. Four Parkinson’s disease patients underwent routine implantation of the subthalamic nucleus. First, local field potentials were recorded in three directions for two conditions: In one condition the patient was at rest, in the other condition the patient’s arm was moved. Second, current thresholds for therapeutic and side effects were identified intraoperatively for directional stimulation. Therapeutic windows were calculated from these two thresholds. Third, the spectral power of the total beta band (13–35 Hz) and its sub-bands low, high, peak beta were analyzed post-hoc. Fourth, the spectral power was used by different algorithms to predict the ranking of directions. The spectral power profiles were patient-specific and spectral peaks were found both in the low beta band (13–20 Hz) and in the high beta band (20.5–35 Hz). The direction with the highest spectral power in the total beta band was most indicative of the 1st best direction when defined by therapeutic window. Based on the total beta band, the resting condition and the moving condition were similarly predictive about the direction ranking and classified 83.3 percent of directions correctly.. However, different algorithms were needed to predict the ranking defined by therapeutic window or therapeutic current threshold. Directional local field potentials may help predict the best stimulation direction. Further studies with larger sample sizes are needed to better distinguish the informative value of different conditions and the beta sub-bands.